Abscisic Acid-Induced Actin Reorganization in Guard Cells of Dayflower Is Mediated by Cytosolic Calcium Levels and by Protein Kinase and Protein Phosphatase Activities - Hwang, Jae-Ung (American Society of Plant Physiologists, 2001)
In guard cells of open stomata under daylight, long actin filaments are arranged at the cortex, radiating out from the stomatal pore. Abscisic acid (ABA), a signal for stomatal closure, induces rapid depolymerization of cortical actin filaments and the slower formation of a new type of actin that is randomly oriented throughout the cell. This change in actin organization has been suggested to be important in signaling pathways involved in stomatal closing movement, since actin antagonists interfere with normal stomatal closing responses to ABA. Here we present evidence that the actin changes induced by ABA in guard cells of dayflower (Commelina communis) are mediated by cytosolic calcium levels and by protein phosphatase and protein kinase activities. Treatment of guard cells with CaCl(2) induced changes in actin organization similar to those induced by ABA. Removal of extracellular calcium with EGTA inhibited ABA-induced actin changes. These results suggest that Ca(2+) acts as a signal mediator in actin reorganization during guard cell response to ABA. A protein kinase inhibitor, staurosporine, inhibited actin reorganization in guard cells treated with ABA or CaCl(2), and also increased the population of cells with long radial cortical actin filaments in untreated control cells. A protein phosphatase inhibitor, calyculin A, induced fragmentation of actin filaments in ABA- or CaCl(2)-treated cells and in control cells, and inhibited the formation of randomly oriented long actin filaments induced by ABA or CaCl(2). These results suggest that protein kinase(s) and phosphatase(s) participate in actin remodeling in guard cells during ABA-induced stomatal closure.